2017
DOI: 10.18805/ijar.b-3274
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and antioxidant response of Lamellidens marginalis exposed to mercuric chloride

Abstract: In recent decades, pollution of freshwater and riverine ecosystems is indorsed to heavy metals contamination. Among various causes, heavy metals are the most concern. Many aquatic organisms have the ability to inhabit in contaminated environments, due to their defense mechanisms that allow detoxification, excretion, anti-oxidant protection and stress response. Lamellidens marginalis have the potential to accumulate the heavy metals. In the present study, the mussels were exposed to 1, 5, 10 and 15 ppm concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Mercury has a strong tendency to revive sulfur and especially thiol-like molecules such as glutathione (GSH), cysteine, and metallothionein. The toxic effects of mercury on organs such as the liver and kidneys are due to biological reactions with metallothionein, glutathione, and albumin [ 5 ]. Many studies showed that oxidative stress caused by mercury exposure (organic and inorganic) results from a reduction in thiol-containing groups, including glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury has a strong tendency to revive sulfur and especially thiol-like molecules such as glutathione (GSH), cysteine, and metallothionein. The toxic effects of mercury on organs such as the liver and kidneys are due to biological reactions with metallothionein, glutathione, and albumin [ 5 ]. Many studies showed that oxidative stress caused by mercury exposure (organic and inorganic) results from a reduction in thiol-containing groups, including glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies showed that heavy metals can influence the LDH activity. For example, Pandy et al found that mercury exposure can reduce the LDH activity in gill of L. marginailis [54]. Akintunde et al found that LDH activity in rat can be reduced by mixed-metal exposure, including Pd, Cd, Co, and Cr [55].…”
Section: Discussionmentioning
confidence: 99%
“…The acute toxicity was studied in fat head minnows (4 mg/lit) by Linda Little [36] . The cytotoxicity was studied in rat L6 cell [42] . From the past few decades, many species have been used as biomonitoring organisms as per their potential.…”
Section: Introductionmentioning
confidence: 99%